Pengembangan Sistem Informasi Pemesanan Daily Catering Senjani Kitchen berbasis Progressive Web App dengan Metode Waterfall - Baariq Fairuuz Azhar; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Senjani Kitchen is a start-up company engaged in food in the city of Malang. Daily Catering Senjani Kitchen uses a coupon system, so customers must buy coupons and exchange the coupons for food according to a schedule. The current condition is that orders are still through the Whatsapp chat application using a smartphone, so customers are too dependent on admin replies. This study aims to develop an information system that aims to make it easier for customers to order food and better record keeping to minimize company losses. Progressive Web App is an application built by optimizing a website, PWA is used so that customers get a more comfortable experience. This development using the waterfall method as a system development life cycle (SDLC). The requirements definition stage produces 2 main business processes, 2 actors, namely customers and admins, and 18 use cases described in use case diagrams and use case specifications. At the system design stage, 18 activity diagrams, sequence diagrams, class diagrams, entity-relationship diagrams, and 26 interface designs were produced. At the implementation stage using the concept of Model View Controller (MVC), React Js as View, and CodeIgniter as Controller and Model. In the testing phase, in the validation test 31 test scenarios run as expected and the usability value is 82.75 (adjective rating excellent) for the customer side and 72.5 (adjective rating good) for the admin side through the usability scale system